2001
DOI: 10.1063/1.1406541
|View full text |Cite
|
Sign up to set email alerts
|

Loading effect in SiGe layers grown by dichlorosilane- and silane-based epitaxy

Abstract: The evolution of the loading effect in Si1−xGex layers (0⩽x⩽20%) versus growth parameters has been investigated for selective and nonselective growth using silane- and dichlorosilane-based epitaxy. Various methods have been examined in order to reduce the loading effect, and their influence on the defect density will be further discussed. High-resolution x-ray diffraction and atomic force microscopy were applied as the main tools in these investigations. It is shown that SiGe epitaxy is strongly sensitive to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
0
28
1
Order By: Relevance
“…25,26 However, other factors such as chemical and thermal effects led to growth rate differences between the bulk and patterned wafers. [27][28][29] The cross-sectional TEM images after selected process cycles are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 However, other factors such as chemical and thermal effects led to growth rate differences between the bulk and patterned wafers. [27][28][29] The cross-sectional TEM images after selected process cycles are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] Here the PureB-layer was deposited at both atmospheric (ATM) and 60 torr on several patterned wafers with ∼80% OCR and opening areas of 100 mm 2 , 200 mm 2 , 300 mm 2 and 400 mm 2 at atmospheric (ATM) and 60 torr. Deposition was performed with different diborane partial pressures and carrier gas flows which P 1 (F 1 ) is the maximum diborane partial pressure (main flow) and P 2 (F 2 ) and P 3 (F 3 ) are 75% and 50% of the maximum values.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we focus on determining the global effects that can be determined on large area windows by using measurement techniques such as SIMS or ellipsometry. While several methods have been proposed to decrease the pattern dependency and/or loading effect for SEG of the Si and SiGe, [8][9][10][11] this is the first report on the reproducibility and the pattern dependency including loading effects of the PureB Deposition. An optimization of the deposition parameters is performed for 700…”
mentioning
confidence: 99%
“…In this way an increase of the amount of oxide area around the window will result in an increase in the PureB-layer thickness. , 45 (6) 39-48 (2012) Impact of deposition parameters on pattern dependency A series of reports on SEG of Si and SiGe, have shown that the pattern dependency can be reduced by tuning the growth parameters (8)(9)(10). Here the PureB-layer was deposited at both atmospheric pressure (ATM) and 60 torr on several patterned wafers with ∼80% OCR and opening areas of 100 mm 2 , 200 mm 2 , 300 mm 2 and 400 mm 2 at atmospheric pressure (ATM) and 60 torr.…”
Section: Effect Of Oxide Coverage and Window Sizementioning
confidence: 99%
“…While several methods have been proposed to decrease the pattern dependency and/or loading effect for SEG of the Si and SiGe (8)(9)(10), this is the first report on the reproducibility and the pattern dependency including loading effects of the PureB depositions. An optimization of the deposition parameters is performed for 700ºC depositions, at either atmospheric (ATM) pressure or 60 torr, with respect to uniformity over the wafer with and without a patterned oxide coverage.…”
Section: Introductionmentioning
confidence: 99%